2016
DOI: 10.1371/journal.pone.0149074
|View full text |Cite
|
Sign up to set email alerts
|

Crippling Violence: Conflict and Incident Polio in Afghanistan

Abstract: BackgroundDesigning effective public health campaigns in areas of armed conflict requires a nuanced understanding of how violence impacts the epidemiology of the disease in question.MethodsWe examine the geographical relationship between violence (represented by the location of detonated Improvised Explosive Devices) and polio incidence by generating maps of IEDs and polio incidence during 2010, and by comparing the mean number of IED detonations in polio high-risk districts with non polio high-risk districts … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
33
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(35 citation statements)
references
References 12 publications
2
33
0
Order By: Relevance
“…We observe low sensitivity of lab-diagnostics (compared to clinical diagnosis) associated with lower social strata and higher homicide risk. However, as with other studies exploring fine-scale relationships between disease and violence [ 65 ], data deficiencies limit sophisticated modeling. In Cali, these deficiencies are likely under-reported in disease surveillance and unavailable or context-poor spatial data on violence.…”
Section: Discussionmentioning
confidence: 99%
“…We observe low sensitivity of lab-diagnostics (compared to clinical diagnosis) associated with lower social strata and higher homicide risk. However, as with other studies exploring fine-scale relationships between disease and violence [ 65 ], data deficiencies limit sophisticated modeling. In Cali, these deficiencies are likely under-reported in disease surveillance and unavailable or context-poor spatial data on violence.…”
Section: Discussionmentioning
confidence: 99%
“…This is supported by the co-location of violent events and polio cases in sub-national areas, including northern Nigeria, southwestern Somalia, and along the Pakistan-Afghanistan border. Our work builds on previous studies by Norris and Kennedy by looking at the additional predictive value of insecurity measures, instead of focusing on the association between violence and polio [ 13 , 14 ]. However, the large number of variables comprising the GPI and FSI make it challenging to isolate the most significant contributing factors, requiring further research into the nuances of political instability.…”
Section: Discussionmentioning
confidence: 99%
“…Their findings suggest a link between post-2011 Islamist insurgencies and polio cases, although not between other conflicts and polio [ 13 ]. Another recent paper examined the relationship between Improvised Explosive Device (IED) detonations and polio, and found a strong association between sites of recent IED explosions and the location of polio cases in recent years in Afghanistan [ 14 ]. These authors conclude that knowledge of the geographic locations of violence can contribute to effective vaccination campaign planning as well as to the successful prediction of future polio incidence.…”
Section: Introductionmentioning
confidence: 99%
“…Armed insurgency has been associated with country-level polio incidence after 2011 (13), however country-level comparisons are limited as polio cases are confined to relatively few countries. Studies in Afghanistan, Sierra Leone, and Angola identified an association between insecurity and reduced vaccination or polio incidence (14)(15)(16)(17), but they are limited in drawing a causal linkage because insecure areas were designated using expert opinion rather than objective data, vaccination rates and polio incidence were not studied together, vaccinator access was not examined, and/or temporal changes in exposure to insecurity were not captured. Numerous articles have commented on the relationship between insecurity and poliovirus transmission (6,12,(18)(19)(20), but none of these provide empirical evidence to support their anecdotal observations.…”
Section: Discussionmentioning
confidence: 99%